Research progress and challenges in prevention and control of combined disasters of coal spontaneous combustion and methane in coal mine goaf - Botao QIN; Dong MA (Meitan xuebao)
The combined disaster of coal spontaneous combustion and methane in coal mine goaf is one of the most serious disasters, often causing significant casualties and economic losses. In order to improve the ability to prevent and control combined disaster in goaf, the air leakage, methane migration and accumulation, and coal spontaneous combustion are summarized as the main forming factors, and the main characteristics of coupling, concealment, uncertainty, dynamicity, secondary and severity has been pointed out. A technology system for prevention and control of combined disaster has been proposed, and the latest research achievements and progress in the dynamic evolution characteristics of coal spontaneous combustion and methane, identification and early warning technology, green and efficient fire prevention and extinguishing technology in goaf, inerting and explosion suppression technology, and emergency response technology have been systematically elaborated. However, with the increasing depth and intensity of coal mining in China, the mining environment undergoes drastic changes, which leads to the problem of composite disasters in goaf areas becoming increasingly serious and complex. Major accidents caused by spontaneous combustion of coal and methane explosions still occur from time to time. In response to the urgent need for efficient prevention and control of coal spontaneous combustion and gas composite disasters in goaf areas, four major challenges are summarized by analyzing the recent combined disasters of coal spontaneous combustion and methane in goaf areas: accurate prediction and evaluation of coupled disaster risk, accurate acquisition of combined disaster information, reasonable selection of enclosed areas, accurate positioning and intelligent targeted disposal of disaster areas. Further, the corresponding research directions and contents are proposed for the efficient prevention and control of coal spontaneous combustion and gas combined disasters in goaf areas, which aims to provide reference for preventing and curbing coal spontaneous combustion and methane combined disasters in goaf areas, and ensure safe and efficient coal mining.